2015
DOI: 10.1093/jxb/erv238
|View full text |Cite
|
Sign up to set email alerts
|

Identification of jasmonic acid-associated microRNAs and characterization of the regulatory roles of the miR319/TCP4 module under root-knot nematode stress in tomato

Abstract: HighlightScreening revealed that the action of miR319/TCP4 in serving as a systemic defensive responder and regulator that modulated the RKN systemic defensive response was mediated via JA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(92 citation statements)
references
References 72 publications
6
85
1
Order By: Relevance
“…The JA signaling pathway is a potent mechanism 439 employed by plants that can defend against necrotrophic and hemibiotrophic pathogens, 440 including the blast pathogen (Thaler, Humphrey et al 2012, Tamaoki, Seo et al 2013 Ding et al 2016). In tomato, miR319 behaves as a systemic signal and a negative regulator of 442 defense responses against RKN through decreasing the JA level (Zhao, Li et al 2015 (Zhang, Ding et al 2016). In our study, JA signaling was induced at the early 446 stage but declined at the late stage (Supplemental Figure S2), which matched the expression 447 pattern of miR319 very well ( Figure 1C).…”
Section: Guy11 Infection Induces Mir319b and Inhibits Ja-mediated Defmentioning
confidence: 99%
“…The JA signaling pathway is a potent mechanism 439 employed by plants that can defend against necrotrophic and hemibiotrophic pathogens, 440 including the blast pathogen (Thaler, Humphrey et al 2012, Tamaoki, Seo et al 2013 Ding et al 2016). In tomato, miR319 behaves as a systemic signal and a negative regulator of 442 defense responses against RKN through decreasing the JA level (Zhao, Li et al 2015 (Zhang, Ding et al 2016). In our study, JA signaling was induced at the early 446 stage but declined at the late stage (Supplemental Figure S2), which matched the expression 447 pattern of miR319 very well ( Figure 1C).…”
Section: Guy11 Infection Induces Mir319b and Inhibits Ja-mediated Defmentioning
confidence: 99%
“…However, the local and systemic accumulation of the wound-responsive proteinase inhibitors and other proteins upon infection of tomato roots by RKNs (39,44) suggest that even nematodes with a stealthy host invasion strategy cause local injury, which subsequently activates defense signaling across compartments. Recently, the screening of miRNA libraries from wild type and the JA-deficient tomato mutant spr2 showed that miR319 targets TCP4 (TEOSINTE BRANCHED1/CYCLOIDAE/PROLIFERATING CELL FACTOR 4) upon RKN infection of the roots (176). Changes may still occur before final publication online and in print that miR319 acts as a systemic signal responder and regulator that connects roots and shoots via its transport in the phloem (Figure 1b).…”
Section: Cross-compartment Signaling and Interactions Induced By Belomentioning
confidence: 99%
“…Several studies hitherto have been conducted on the development of strategies and identification of miRNA targets to control plant-parasitic nematodes [14,15,16]. In the context of PPNs, the availability of the whole genome sequence of M. incognita [17] has led to several investigations focusing on elucidating potential miRNAs that can be used to control the pest in plants.…”
Section: Introductionmentioning
confidence: 99%